Parallel performance analysis of bacterial biofilm simulation models - Sheraton, Muniraj Vivek (2019)
Modelling and simulation of bacterial biofilms is a computationally expen-sive process necessitating use of parallel computing. Fluid dynamics and ad-vection-consumption models can be decoupled and solved to handle the flu-id-solute-bacterial interactions. Data exchange between the two processes add up to the communication overheads. The heterogenous distribution of bacteria within the simulation domain further leads to non-uniform load dis-tribution in the parallel system. We study the effect of load imbalance and communication overheads on the overall performance of simulation at dif-ferent stages of biofilm growth. We develop a model to optimize the parallel-ization procedure for computing the growth dynamics of bacterial biofilms.